KESULITAN KESULITAN SISWA SMP KELAS VIII DALAM MEMAHAMI KONSEP MATEMATIKA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARRIABEL (SPLDV) - Puji Astuti (MEGA: Jurnal Pendidikan Matematika, 2023)
Abstract This study aims to determine the difficulty of students in class VIII in understanding the understanding of mathematical concepts in the system of linear two-variable equations and the principles experienced by students in solving the problem stories for two-variable linear equation systems and the factors that cause students to experience these difficulties. The method used in this research is descriptive method. The subjects used in this study were students of class VIII selected with consideration. The instrument used is a written test in the form of essays and interview guidelines. From the data analysis, it is known the difficulties and the factors causing the difficulties experienced by students. difficulty in converting story problems into mathematical sentences, difficulty in operating with the substitution method, difficulty in operating addition and subtraction. The factors that cause difficulties are the lack of mastery of the system of linear equations for the two variables SPLDV, the lack of persistence, lack of accuracy when working on the questions, do not master the concept of the linear system for the two variables SPLDV.